Influence of SME characteristics on the implementation of ERP - Omar Khadrouf; Marieme Chouki; Mohamed Talea; Assia Bakali (Universitas Ahmad Dahlan, 2020)
The ERP market has recently experienced a significant evolution in recent years, both in large companies and in small and medium-sized enterprises (SMEs). Compared to large companies, SMEs are distinguished by specific characteristics that can influence the implementation of the ERP system in these organizations. The purpose of this study is to analyse how these characteristics can determine the success or the failure of ERP implementation in SMEs. First, a set of characteristics, specific to SMEs has been identified from the relevant literature. Then, the influence of each characteristic on the different ERP lifecycle activities were studied. A multiple case study of four SMEs from different sectors was conducted. The data collection was carried out through 28 individual interviews with several stakeholders (users, external consultants, internal IT specialists and managers) in the four cases. The analysis of the interview data showed first that financial resources, Decision making and, the type of ownership of the company were identified as the most influential contextual factors. Then the two phases of the ERP life cycle